Results of preventive treatment of tuberculosis in HIV infected patients in Nizhny Novgorod Region - G. F. Rusanovskaya; S. V. Minaeva; N. N. Sidorova; V. A. Balaganin; S. A. Аpoyan (Туберкулез и болезни лёгких)
The objective: to analyze the results of preventive treatment (PT) of tuberculosis in HIV infected patients in Nizhny Novgorod Region.Subjects and methods: in 2015-2017, preventive treatment of tuberculosis was prescribed to 1,374 people living with HIV (PLHIV), registered in TB dispensaries. Before the prescription of preventive treatment, patients underwent a comprehensive examination to exclude active tuberculosis, including digital chest X-ray. For immunodiagnostics of latent tuberculosis infection, an intradermal Mantoux test with 2 TU of puriﬁed tuberculin in standard dilution was used. The immune status was assessed based on CD4+ count. The eﬀectiveness of antiretroviral therapy (ARVT) was assessed by the concentration of HIV RNA in the blood; when achieving complete viral suppression (less than 58 copies of HIV RNA in μl), ARVT was found to be eﬀective. Preventive treatment included isoniazid at a dose of 5 mg per kg of patient body weight in combination with vitamin B6 (pyridoxine hydrochloride) at the dose of 15-25 mg/day (tablet) for 6 months.Results. The eﬃcacy of preventive treatment was assessed by 2-year survival free of active tuberculosis in those who started preventive treatment (including those who did not complete it). There were organizational problems while administering preventive treatment of tuberculosis people living with HIV: low adherence to treatment, diﬃculties in monitoring drug in-take and adverse events monitoring. Only 601/1,374 – 43.7% of people completed the entire 6-month course. Tuberculosis developed in 10 (0.7 ± 2.7%) of 1,374 PLHIV who started preventive treatment, of which 9/10 at that time had CD4+ count below 350 cells/μl, and 8/10 patients refused or interrupted ART. Among PLHIV who completed the 6-month course of preventive treatment, 1 of 601 (0.17%) developed tuberculosis, while among those who interrupted – 9/773 (1.16%) (χ2 = 4.66; p < 0.05), which made 170 and 1,160 per 100,000 decreed population, respectively. The presented results allow concluding that preventive treatment of tuberculosis is advisable for PLHIV.